An observational study on the effect of premature ventricular complex burden on long-term outcome. Issue 1 (January 2017) - Lin, Chin-Yu; Chang, Shih-Lin; Lin, Yenn-Jiang; Chen, Yun-Yu; Lo, Li-Wei; Hu, Yu-Feng; Tuan, Ta-Chuan; Chao, Tze-Fan; Chung, Fa-Po; Liao, Jo-Nan; Chang, Yao-Ting; Lin, Chung-Hsing; et al.
Abstract : Abstract: The long-term clinical impact of premature ventricular complexes (PVCs) on mortality and morbidity has not been fully studied. This study aimed to investigate the association between the burden of PVCs and adverse clinical outcome. A total of 5778 subjects, who were pacemaker-free and ventricular tachycardia-free at baseline, received 24-hour electrocardiography monitoring between January 1, 2002 and December 31, 2004. Clinical event data were retrieved from the Bureau of National Health Insurance of Taiwan. Multivariate Cox hazards regression models and propensity-score matching were applied to assess the association between PVCs and adverse clinical outcome. Average follow-up time was 10± 1 year. In all, 1403 subjects expired, 1301 subjects were hospitalized in the cardiovascular (CV) ward, 3384 were hospitalized for any reason, and 631 subjects developed new-onset heart failure (HF). The optimal cut-off PVC frequency (12 beats per day) was obtained through receiver operator characteristic curves, with a sensitivity of 58.4% and specificity of 59.8%. Upon multivariate analysis, a PVC frequency >12 beats per day was an independent predictor for all mortality (hazard ratio [HR]: 1.429, 95% confidence interval [CI]: 1.284–1.590), CV hospitalization (HR: 1.127, 95% CI: 1.008–1.260), all-cause hospitalization (HR 1.094, 95% CI: 1.021–1.173), and new-onset HF (HR: 1.411, 95% CI: 1.203–1.655). Subjects with a PVC frequency >12 beats per day had an increased risk of cardiac death attributable to HF and sudden cardiac death. The incidence rates for mortality and HF were significantly increased in cases of raised PVC frequency. Propensity-score matching analysis also echoed the main findings. Increased PVC burden was associated with a higher incidence of all-cause mortality, CV hospitalization, all-cause hospitalization, and new-onset HF which was independent of other clinical risk factors.